MUDPOTS AT STEFANOS HYDROTHERMAL CRATER OF NISYROS VOLCANO. AN INSIGHT AT THE HYDROTHERMAL PROCESSES OF AN ACTIVE VOLCANO - Kanellopoulos, C.; Xirokostas, N. (Bulletin of the Geological Society of Greece, 2016)
On Nisyros island as a result of the volcanic activity and active tectonic, a hydrothermal system develops and it is expressed by 5 types of surface manifestations: i) thermal springs, ii) fumaroles iii) hydrothermal craters, iv) hot grounds and v) mudpots. In general, a mudpot could be described as an acidic hot spring and fumarole with limited water which it is formed in high temperature geothermal areas. Water sample and depositions of mudpots collected, analyzed and studied from Stefanos hydrothermal crater, which is the only site on Nisyros Island, where mudpots occur. Mudpots water is very acidic (pH=2.4), with high sulfate concentration (1375mg/L), due to the H2S(gas) and temperature near the boiling point. As a result, elemental sulfur is found inside the depositions alongside with products of the hydrothermal alteration of the surrounding rocks. In the water and in the depositions were found high concentrations in several elements (e.g. in water: 55mg/L Fe; 19.5mg/L Zn, in depositions: 430mg/Kg Pb; 72mg/Kg Cu; 60mg/Kg Cr) reflecting the alterations processes which are taking place.